The Direct Effect of Whale Shark Ecotourism on The Social Economy of The Community in Sumbawa Indonesia - Nila Wijayanti; Sri Nurhidayati; Sri Rahayu; Ieke Wulan Ayu; Edrial Edrial (Journal of Global Sustainable Agriculture, 2024)
This research wants to find out about the direct influence of whale shark ecotourism on the social economy of the people in Sumbawa. The study is held at the Labuhan Jambu Tourism Village, Tarano District, Sumbawa Regency, West Nusa Tenggara. Data sources were available from primary and secondary data. This research was analyzed using the Structural Equation Model-Partial Least Squares (SEM.WarpPls). The number of samples used in the study was 70 people. The research results show that the direct relationship between x1 (MSME entrepreneurs) and y1 (changes in community behavior) is significantly positive. A significant positive relationship also occurs between x2 (visitors to the Whale Shark tourist park) and y3 (community welfare). The direct relationship between x1 (MSME entrepreneurs) with y2 (changes in the community economy) and y3 (community welfare) is not significant. An insignificant relationship also occurs between x2 (visitors to the Whale Shark tourist park), y1 (changes in community behavior), and y2 (changes in the community's economy). The direct relationship between x3 (government) and x4 (stakeholders) with y1 (changes in community behavior), y2 (changes in the community economy), and y3 (community welfare) is also not significant. These results indicate that the existence of Whale Shark ecotourism does not have a direct effect on the social economy of the community.